JMHM Editorial Office Participates in the 2025 Annual Conference of the Health Communication Committee (The Journal of Medicine, Humanity and Media, 2025)
The 2025 Annual Conference of the Health Communication Committee under the Chinese Association for History of Journalism and Communication was successfully held on September 13 at Northwest Minzu University in Lanzhou, Gansu Province.